Forest structure and territory size relationship in the neotropical understorey insectivore Henicorhina leucosticta - Vargas, Luis Esteban (2010)
The neotropical terrestrial insectivore Henicorhina leucosticta (Troglodytidae) maintains long-term territories through vocalizations and forages among leaf litter trapped in the understorey vegetation and ground litter. The relationship between forest structure and H. leucosticta territory size was studied in La Selva Biological Station, Costa Rica, during the non-breeding season in 2009. Forest structure was measured by assessing canopy openness and leaf area index (LAI) using hemispherical photography, while territory size was estimated with the playback technique using local conspecific vocalizations. Mean territory area was 3.8 ± 2.8 ha (mean ± SD, n = 10). Territory radius length was similar in old-growth forest and abandoned agro-forest plantations. We found that H. leucosticta territory size decreased as median LAI increased. We propose that LAI is related to territory size through the amount of leaf fall and subsequent leaf litter accumulation over the understorey plants, which constitutes an important reservoir of arthropod prey and nest materials for H. leucosticta. The long-term supply of food resources is likely to affect territory size in this species, as well as other insectivorous birds with similar foraging behaviour. These results are congruent with the structural cues hypothesis.